Ensila Plus, Sila-lator, and Silo-Guard for alfalfa silage - Bolsen, K.; Ilg, H. (Kansas State University. Agricultural Experiment Station, 2011)
Four alfalfa silages (34 to 37% DM) were made May 30 and 31, 1979, as follows: 1) no additive (control), 2) 3 ounces of Ensila Plus per ton, 3) 1.0 lb of Si1a-1ator per ton, and 4) 1.5 1b of Silo-Guard per ton. Silos were opened after 51 days and each was fed to 41 bred, yearling heifers (one pen of 20 and one pen of 21) during a 26-day trial (July 21 to August 16, 1979). All heifers also received 2.0 1bs daily of a grain mix that contained 200 mg of Rumensin for one pen fed each silage and no Rumensin for the other pen. The silages were full-fed so that the two pens (Rumensin or no Rumensin) receiving each silage got approximately the same quantity of feed. Ensiling temperatures, fermentation dry matter losses, and stability when exposed to air were determined for each silage.
Keywords: Beef; Alfalfa silage; Dry matter; Temperature; Fermentation; Stability